STRUKTUR MOLEKUL SENYAWA ASAM 3,4 SECO BRIONONAT DALAM KULIT BATANG TANAMAN KECAPI KERA Sandoricum emarginatum Hiern - Pratiwi Pudjiastuti (JURNAL PENELITIAN BIOLOGI BERKALA PENELITIAN HAYATI, 1995)
Kecapi kera (Sandoricum emarginatum Hiern) is a plant grow in Sumatera, Indonesia bong the familia Meliaceae. There are two species of Sandoricum in Indonesia, Sandoricum koetjape and Sandoricum emarginatum. The S.koetjape plant has been investigated and contains some chemical compounds and there are two of which have a cytotoxic activity to the cell culture P 388 but Sandoricum emarginatum not yet investigated. The aim of this research was to determine the molecular structure compound of stem bark of Kecapi kera which soluble in chloroform. The chemical compound in stem bark of Kecapi kera was extracted with petroleum ether, chloroform, and methanol, respectively. Chloroform fraction was separated and isolated with column chromatography, n-hexane-ethyl acetate as mobile phase and silica gel as stationary phase. Molecular structure determination was carried out using spectroscopy method such IR, NMR, and MS. As the result a white crystal, 3,4-seco bryo-nonat could be isolated. The crystal has a needle like form and had melting point between 226-228oC.